Evapotranspiration of rubber (Hevea brasiliensis) cultivated at two plantation sites in Southeast Asia. Issue 2 (4th February 2016) - Giambelluca, Thomas W.; Mudd, Ryan G.; Liu, Wen; Ziegler, Alan D.; Kobayashi, Nakako; Kumagai, Tomo'omi; Miyazawa, Yoshiyuki; Lim, Tiva Khan; Huang, Maoyi; Fox, Jefferson; Yin, Song; Mak, Sophea Veasna; et al.
Abstract: To investigate the effects of expanding rubber ( Hevea brasiliensis ) cultivation on water cycling in Mainland Southeast Asia (MSEA), evapotranspiration ( ET ) was measured within rubber plantations at Bueng Kan, Thailand, and Kampong Cham, Cambodia. After energy closure adjustment, mean annual rubber ET was 1211 and 1459 mm yr −1 at the Thailand and Cambodia sites, respectively, higher than that of other tree‐dominated land covers in the region, including tropical seasonal forest (812–1140 mm yr −1 ), and savanna (538–1060 mm yr −1 ). The mean proportion of net radiation used for ET by rubber (0.725) is similar to that of tropical rainforest (0.729) and much higher than that of tropical seasonal forest (0.595) and savanna (0.548). Plant area index (varies with leaf area changes), explains 88.2% and 73.1% of the variance in the ratio of latent energy flux (energy equivalent of ET ) to potential latent energy flux ( LE / LEpot ) for midday rain‐free periods at the Thailand and Cambodia sites, respectively. High annual rubber ET results from high late dry season water use, associated with rapid refoliation by this brevideciduous species, facilitated by tapping of deep soil water, and by very high wet season ET, a characteristic of deciduous trees. Spatially, mean annual rubber ET increases strongly with increasing net radiation ( Rn ) across the three available rubber plantation observation sites, unlike nonrubber tropical ecosystems, which reduce canopy conductance at high Rn sites. High water use by rubber raises concerns about potential effects of continued expansion of tree plantations on water and food security in MSEA. Key Points: SE Asian rubber plantations maintain very high annual evapotranspiration (ET) Access to deep soil water enables rapid refoliation after leaf drop and high late dry season ET Spatially rubber evapotranspiration increases linearly with increasing net radiation